2012
DOI: 10.1111/j.1365-2915.2012.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diversity and abundance of fleas and mites in the Neotropics: host‐related, parasite‐related and environment‐related factors

Abstract: The effects of host-related, parasite-related and environmental factors on the diversity and abundance of two ectoparasite taxa, fleas (Insecta: Siphonaptera) and mites (Acari: Mesostigmata), parasitic on small mammals (rodents and marsupials), were studied in different localities across Brazil. A stronger effect of host-related factors on flea than on mite assemblages, and a stronger effect of environmental factors on mite than on flea assemblages were predicted. In addition, the effects of parasite-related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…In nonhuman primates, Nunn et al (2005) found no significant relationship between parasite species richness and latitude when all parasite types were combined, and only protozoan species richness was significantly and negatively correlated with latitude when analyzed separately. Using small mammals from Brazil, Linardi and Krasnov (2013) found that flea species richness was not significantly related to latitude and mite species richness was significantly and positively correlated with latitude, with mite richness increasing with distance from the equator. Further, when parasite species were broken down into groups of helminths, protozoa, bacteria and viruses, only helminth species richness was positively and significantly correlated with latitude (Lindenfors et al 2007).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 91%
See 1 more Smart Citation
“…In nonhuman primates, Nunn et al (2005) found no significant relationship between parasite species richness and latitude when all parasite types were combined, and only protozoan species richness was significantly and negatively correlated with latitude when analyzed separately. Using small mammals from Brazil, Linardi and Krasnov (2013) found that flea species richness was not significantly related to latitude and mite species richness was significantly and positively correlated with latitude, with mite richness increasing with distance from the equator. Further, when parasite species were broken down into groups of helminths, protozoa, bacteria and viruses, only helminth species richness was positively and significantly correlated with latitude (Lindenfors et al 2007).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 91%
“…Distributed worldwide, rodents are often involved in zoonotic disease cycles and are expected to become the most prevalent mammals in environments with increasing anthropogenic changes (Bordes et al 2015), yet investigations of the biogeographical patterns of much of their parasite fauna are lacking (but see Krasnov et al 2004, Linardi andKrasnov 2013). Distributed worldwide, rodents are often involved in zoonotic disease cycles and are expected to become the most prevalent mammals in environments with increasing anthropogenic changes (Bordes et al 2015), yet investigations of the biogeographical patterns of much of their parasite fauna are lacking (but see Krasnov et al 2004, Linardi andKrasnov 2013).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 99%
“…Other sex and age preferences result from grooming because males are more efficient groomers than females and adults groom more than young individuals. Regarding environmental factors, Linardi and Krasnov (2013) observed that in three hosts ( Monodelphis domestica , Necromys lasiurus , and Oligoryzomys eliurus ) collected at different localities across Brazil, the mean flea abundance significantly increased with an increase in the mean annual air temperature and the proximity to the equator. For both M. domestica and N. lasiurus , abundance also decreased with altitude.…”
Section: Infestationmentioning
confidence: 99%
“…Most factors fall broadly into 2 categories: host factors and environmental factors. Host factors encompass a range of attributes, including individual-level properties (such as sex, age, body condition, and health), species-level properties such as taxonomy and life history (e.g., body size, longevity, sociality), and community-level properties such as host density and host composition and diversity (Krasnov et al, 2002c;Stanko et al, 2002;Linardi and Krasnov, 2013).…”
mentioning
confidence: 99%
“…The relative importance of host versus environmental factors in driving prevalence and intensity of flea parasitism may vary based on spatial scale, while effects operating at different scales may in turn interact (Linardi and Krasnov, 2013). In this study, we examine the relative importance of a suite of both environmental and host factors in explaining variation in the intensity and prevalence of flea parasitism across small mammal communities in central Kenya.…”
mentioning
confidence: 99%